The Influence of Wages, Workload and Non-Physical Work Environment on Worker Loyalty in the Tarutama Nusantara Jember Agribusiness Cooperative - M Iqbal Maulana; Trias Setyowati; Septy Holisa Umamy (Fakultas Ekonomi Universitas Muhammadiyah Palu, 2024)
The study aims to identify and analyze the impact of wages, workload and non-physical work environment on labour loyalty in Tarutama Nusantara Jember Agribusiness Cooperation. The location of this research is Sub Devisi Pancakarya C, Jl Semeru, Pancakariya, Ajung-Jember, East Java. This type of research uses a quantitative method with a sample number of 85 freelance respondents and a nonprobability sampling technique with a saturated sampler technique using a data collection technique in the form of a questionnaire to respondents, for the analysis techniques of this research data using instrument testing, classical assumptions and double linear regression. The results of the analyses obtained showed that wages, workload and non-physical work environment have a positive and significant impact both partially and simultaneously on the loyalties of the freelance labour force to the Tarutama Nusantara Jember Devisi Sub Pancakarya C Agribusiness Cooperation, with a Contribution Rate of influence of 0.434 or 43.3%.